Long-Term Outcomes of Sternal-Sparing Versus Sternotomy Approaches for Mitral Valve Repair: Meta-Analysis of Reconstructed Time-to-Event Data. Issue 2 (March 2023) - Sá, Michel Pompeu; Jacquemyn, Xander; Erten, Ozgun; Van den Eynde, Jef; Caldonazo, Tulio; Doenst, Torsten; Ruhparwar, Arjang; Weymann, Alexander; de Souza, Rodrigo Oliveira Rosa Ribeiro; Rodriguez, Roberto; Ramlawi, Basel; Goldman, Scott
Objective: Since there are concerns about the durability of mitral valve repair (MVRp) with minimally invasive techniques in patients with mitral regurgitation (MR), we aimed to evaluate the long-term outcomes of these sternal-sparing approaches when compared with conventional approaches with sternotomy in patients undergoing MVRp. Methods: We performed a systematic review according to a preestablished protocol and performed a pooled analysis of Kaplan–Meier–derived reconstructed time-to-event data from studies with longer follow-up comparing sternal-sparing versus sternotomy approaches for MVRp. Our outcomes of interest were survival, freedom from recurrent MR, and freedom from reoperation. Results: Eleven studies met our eligibility criteria comprising 7, 596 patients with follow-up (sternal sparing, n = 4, 246; sternotomy, n = 3, 350). Patients who underwent sternal-sparing MVRp had a significantly lower risk of mortality over time compared with patients who underwent MVRp with sternotomy (hazard ratio [HR] = 0.29, 95% confidence interval [CI]: 0.23 to 0.36, P < 0.001) in the overall analysis. However, we found no statistically significant difference between the groups in the sensitivity analysis with adjusted populations (HR = 0.85, 95% CI: 0.63 to 1.15, P = 0.301). Regarding the outcomes freedom from recurrent MR and freedom from reoperation, we found no statistically significant differences between the groups in the follow-up in both overall and sensitivity analyses. Conclusions: In comparison with MVRp with sternotomy approaches, sternal-sparing MVRp was not associated with worse outcomes in terms of survival, recurrent MR, and reoperations over time. Visual abstract